The peaceful wave = 靜靜的漣漪 : a study of the history of Ningbo 1820s-1949 - Sun, Bowen (2020)
This thesis examines the gradual declining trend of the state level influence over the local development in Ningbo during most of the 19th century, and how a few local institutions at the society level responded to their own opportunities and difficulties during the Republican era while a newly authoritative regime gradually emerged. This thesis will also suggest that academic scholarship concerning the study of Ningbo’s history had underestimated the West’s and the Westernised Japan’s stimulating impacts over Ningbo’s economic and social development during the late Qing and early Republican era.